PROSPEK DAN TANTANGAN PEREKONOMIAN INDONESIA: TANTANGAN DEMOGRAFI DAN GEOPOLITIK MENUJU INDONESIA EMAS 2045: Toward Indonesia Emas 2045: Integrating Demographic Dividend and Geopolitical Risk through Islamic Social Finance - Badrus Soleh; Fadil hakiki Fadil; Dahruji; Agus Naidi (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2026)
Indonesia faces a critical challenge in balancing its 2045 development ambitions amidst escalating global Geopolitical Risks (GPR), geo-economic fragmentation, and the urgency of managing the demographic dividend. Conventional fiscal and monetary instruments often suffer from recognition and implementation lags, pro-cyclical bias, and debt-driven vulnerabilities when responding to external shocks. Objective: This study aims to formulate an integrated and Maqasid-based macroeconomic stabilization framework by leveraging Islamic Social Finance (ISF) as a systemic automatic stabilizer. Methods: Using a Qualitative Systematic Literature Review (SLR) with the PRISMA protocol on 22 reputable academic works (2015–2025), this research identifies structural gaps in conventional stabilization policies that remain highly exposed to external volatility and output gap widening. Results: The study proposes the Zakat-Integrated Automatic Stabilizer (ZIAS) model, which operates through a dual-trigger mechanism—responding to the Geopolitical Risk (GPR) index as a forward-looking exogenous trigger and domestic macro indicators (such as unemployment and output gap) as endogenous realized-stress triggers. The model demonstrates that zakat, through its counter-cyclical and redistributive nature combined with a high marginal propensity to consume among beneficiaries, functions as a community-based shock absorber that stabilizes aggregate demand and protects human capital without increasing the national debt burden. Conclusion: Institutionalizing ISF within a Maqasid al-Shari’ah-based national macroeconomic architecture is essential to strengthen intergenerational resilience and ensure the sustainability of human capital investment toward Indonesia Emas 2045.